Approaches related to the effects of Covid-19 pandemics on financing of the healthcare system in Romania - Antohi, Valentin Marian; Ionescu, Romeo Victor; Zlati, Monica Laura; Mirica, Cristian (Frontiers in Public Health, 2022)
Background The healthcare financial system faced a significant disturbance of the budget balance after the outbreak of the pandemic, amid government measures to combat the disease. These measures have led to shifts in funding weights within the income and expenditure budget structure, with a focus on prevention and treatment of patients infected with SARS-COV 2. The purpose of this research is to analyse the financial balance of the healthcare system and the related modelling to support decision-makers in adopting and implementing appropriate financing measures for the pandemic. Methods The working hypotheses of this study were tested using an econometric linear regression model based on the financing budgetary function, which matches funding to the specific need for each expenditure heading. SPSS 25 statistical software was used to define the model and to test the homogeneity of the data and their statistical relevance to the phenomenon under analysis. Results The proposed model showed that there is a significant correlation of the dependent variable, Dynamics of budget revenues in the healthcare sector (TIM), with the regressors. We believe that a problem-solving rebalancing of allocations could help to eliminate the synergy in health. This redistribution should take into account the impact that economic and budgetary factors have on healthcare factors and vice versa, so that at some point after successive adjustments the minimum distance between forecast and realisation or between need and financing of need can be reached. The used data were analysed dynamically to assess changes in trend as absolute data do not allow the construction of an overall picture. Relative data captures changes in financing from year to year and can be linked to events such as pandemics, financial crises or inflation. Conclusions In relation to the objectives of the research, it emerges that, under the impact of pandemic stress, measures to improve healthcare management, increase performance and streamline financial allocation are vulnerable and cannot counteract the effects that the pandemic has on the healthcare of the population as reflected in the morbidity and mortality indicators collected during the pandemic. In this regard, it is necessary a rethinking of the strategic healthcare management, a better planning of the procurement of medicines and healthcare supplies, a rethinking of the partnerships with the European Commission and other global entities. This approach can effectively improve the impact of the pandemic on the healthcare status of the population, a rebalancing of the demand-supply balance in healthcare and a maintenance of the strategic programmes, according to the objectives assumed in the planning, given that these programmes protect categories of people already medically affected.